Improving Students’ Speaking Skill through Storytelling Technique at Tenth Grade Of SMAN 09 Kota Tangerang In Academic Year 2020/2021 - Widyasari, Nova; Isnaniah, Isnaniah (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2021)
ABSTRACT This research was conducted at SMAN 09 Kota Tangerang. The aim of this research was to find out whether there is a significant effect of storytelling technique on students’ speaking skill. The population of this research was the tenth-grade students’ of SMAN 09 Kota Tangerang. The samples are 36 students of X IPS 3. This research used Quasi-Experimental. The research data is collected through pre-test and post-test. It used statistical calculation by One-Sample Kolmogorov-Smirnov test. It is known the asymptotic significances of the pre-test and post-test in experimental class data. The result of this research showed that students’ confidence in speaking was improved by using storytelling technique. Most of them are more active in the speaking classroom. Hence, it can be concluded that there is a positive impact of Storytelling Technique on students’ speaking skill at the tenth grade of SMAN 09 Kota Tangerang in academic year 2020/2021.